TANGGUNG JAWAB PELAKU USAHA ATAS PEREDARAN KOSMETIK TANPA IZIN EDAR DIKAITKAN DENGAN PERLINDUNGAN KONSUMEN - Eva Komala Sari (2022)
Cosmetics are substances or mixtures of materials used on the body for the purpose of cleaning, maintaining, and increasing attractiveness. The Food and Drug Supervisory Agency is an institution in Indonesia that was formed based on Presidential Decree No. 3 of 2013. This study aims to analyze the responsibility of business actors for the distribution of cosmetics without a marketing permit in relation to consumer protection, juridically normatively against the distribution of cosmetics without a marketing permit which is detrimental. consumers and the responsibility of business actors for the distribution of cosmetics without a distribution permit. This study aims to find out how the procedures for distributing cosmetics by business actors in Indonesia according to laws and regulations are in order to be able to analyze the steps of cosmetic procedures before they are distributed and also to know the importance of the responsibility of business actors for the distribution of cosmetics without a marketing permit which is associated with consumer protection. In this study using normative juridical law research, the data used are secondary data, data collection techniques using literature studies and interviews with one of the staff of the Jakarta Food and Drug Administration. This analysis is in accordance with the provisions of Law Number 8 of 1999 concerning Consumer Protection, Law Number 36 of 2009 concerning Health, Government Regulation Number 72 of 1998 concerning Pharmaceutical Preparations, and the Decree of the Head of the Drug and Food Control Agency. The results of the study found that there were still many cosmetics that were not in accordance with predetermined standards, so that there were still many people who used cosmetics without a marketing authorization and fake and dangerous cosmetics. If a business actor intentionally distributes, sells and buys cosmetic products without having a notification number, they will be subject to sanctions in the form of administrative sanctions and criminal sanctions